Development Of Future Vocational Teachers in The Process of Modernization on The Basis of Scientific Integration of General Professional and Special Competencies (Journal of Pedagogical Inventions and Practices, 2022)
This article describes the formation and content of professional competence in future vocational education teachers, the role and importance of basic competencies in their preparation for professional activity, the formation of students' knowledge, skills and abilities in general and specialized subjects, pedagogical and technical knowledge